Optimal planning for container prestaging, discharging, and loading processes at seaport rail terminals with uncertainty - Xie, Ying; Song, Dong-Ping (Transportation research. Part E, Logistics and transportation review, 2018)
•Simultaneously optimise container prestaging and container flow rates at seaport rail terminals.•Obtain the optimal strategy using the stochastic dynamic programming.•Propose four simplified strategies that are computationally efficient and readily applicable.•Illustrate the results in a case study of seaport rail terminals. This paper considers the optimal planning problem for container prestaging and dynamic discharging/loading at seaport rail terminals subject to uncertainties. We formulate the problem into a stochastic dynamic programming model to minimise the total logistics cost. Four simplified strategies are proposed. Experiments based on a real case study are performed to compare the optimal strategy with four simplified strategies in terms of cost, computing time and practicality. Results show that the seaport can use prestaging to reduce the cost involved and that an appropriate discharging/loading plan can be created in response to different prestaging situations and uncertain scenarios.